Pengalaman Negatif Pendidik Sebaya Kelompok Kunci Lelaki Seks dengan Lelaki dalam Memberikan Layanan Pencegahan HIV: Negative Experiences of Key Group Peer Educators of Men who have Sex with Men in Providing HIV Prevention Services - Mahathir; Bunga Permata Wenny; Nurlita; Lutfiah Khairunnisa (Fakultas Keperawatan Universitas Andalas, 2024)
Peer support programmes have been shown to have a substantial impact on overall HIV outreach efforts. Peer educators have played an essential part in the HIV response, despite a number of challenges and negative experiences throughout implementation. These adverse experiences are often ignored and poorly documented, leaving peer educators vulnerable. The aim of this study is to explore the negative experiences of peer educators in reaching out to men who have sex with men (MSM). This research used a qualitative phenomenological study design. This study involved thirty-six peer educators that work in several non-government organizations. Three focus group discussions were conducted in September 2023 to Desember 2023. The Stevick-Colaizzi-Keen data analytical method was used for data analysis. Five themes regarding the peer educators’ negative experiences whilst interacting with the MSM population were obtained from the data analysis. The themes were experiencing discriminatory conduct, abuse, humiliation, cancel the meeting, and incurred personal expenses. In order to accomplish HIV prevention through case finding and treatment milestones, peer educators are dedicated to working with a wide range of MSM groups. Peer educators may need to develop certain coping mechanisms to get through uncomfortable circumstances. In order to deal with unpleasant situations sensibly, it is vital to provide adequate support and protection recommendations, as well as having awareness of self-defence mechanisms.